The Influence of learning motivation, learning styles, and learning interests on student achievement in Islamic religious education - Syahrani, Amellia Putri; Dewi, Eva; Muslim (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2026)
This study aims to analyze the influence of learning motivation, learning styles, and learning interest on student learning outcomes, both partially and simultaneously, in the Islamic Education (PAI) subject at SMK Negeri 2 Pekanbaru. The study was conducted at SMK Negeri 2 Pekanbaru using a quantitative correlational method through a field survey design and an ex post facto approach. The study population consisted of students at SMK Negeri 2 Pekanbaru, with a sample of 70 students from class X.5 selected using purposive sampling, comprising 52 male students (74.3%) and 18 female students (25.7%). All instruments were tested for validity using the Product Moment test and for reliability using Cronbach’s Alpha. Data analysis techniques included Pearson correlation analysis and multiple regression. The results of the correlation analysis showed that learning style (r = 0.449; p = 0.000) and learning interest (r = 0.580; p = 0.000) had a positive and significant relationship with learning outcomes, while learning motivation showed a non-significant relationship (r = 0.075; p = 0.540). The results of the multiple regression analysis indicate that the research model is simultaneously significant (F=11.321; p<0.05) with an R² value of 0.340, meaning that the three independent variables account for 34% of the variance in learning outcomes. Partially, only learning interest had a significant effect on learning outcomes (β=0.526; t=3.715; p=0.000), while learning motivation (β=-0.010; p=0.918) and learning style (β=0.079; p=0.579) did not have a significant effect. It is hoped that the results of this study can serve as a basis for schools to design more effective learning strategies, particularly in enhancing students’ interest in learning as a key factor in improving learning outcomes in the Islamic Education subject at SMK Negeri 2 Pekanbaru. Abstrak Penelitian ini bertujuan untuk menganalisis pengaruh motivasi belajar, gaya belajar, dan minat belajar terhadap hasil belajar siswa, baik secara parsial maupun simultan pada mata Pelajaran PAI di SMK Negeri 2 Pekanbaru. Penelitian dilakukan di SMK Negeri 2 Pekanbaru dengan menggunakan metode kuantitatif korelasional melalui desain survey lapangan dan pendekatan ex post facto. Populasi penelitian adalah siswa SMK Negeri 2 Pekanbaru, dengan sampel sebanyak 70 siswa dari kelas X.5 yang dipilih menggunakan teknik purposive sampling, terdiri dari 52 siswa laki-laki (74,3%) dan 18 siswa perempuan (25,7%). Semua instrumen telah diuji validitas menggunakan uji Product Moment dan reliabilitas menggunakan Alpha Cronbach. Teknik analisis data menggunakan analisis korelasi Pearson dan regresi berganda. Hasil analisis korelasi menunjukkan bahwa gaya belajar (r=0,449; p=0,000) dan minat belajar (r=0,580; p=0,000) memiliki hubungan positif dan signifikan dengan hasil belajar, sedangkan motivasi belajar menunjukkan hubungan yang tidak signifikan (r=0,075; p=0,540). Hasil analisis regresi berganda menunjukkan bahwa model penelitian secara simultan signifikan (F=11,321; p<0,05) dengan nilai R²=0,340, yang berarti ketiga variabel independen mampu menjelaskan 34% varians hasil belajar. Secara parsial, hanya minat belajar yang berpengaruh signifikan terhadap hasil belajar (β=0,526; t=3,715; p=0,000), sedangkan motivasi belajar (β=-0,010; p=0,918) dan gaya belajar (β=0,079; p=0,579) tidak berpengaruh signifikan. Hasil penelitian ini diharapkan dapat menjadi dasar bagi pihak sekolah untuk merancang strategi pembelajaran yang lebih efektif, khususnya dalam meningkatkan minat belajar siswa sebagai faktor kunci peningkatan hasil belajar pada mata Pelajaran PAI di SMK Negeri 2 Pekanbaru.